2010
DOI: 10.1177/1066480710371795
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of Conflict and Control: A Conceptualization of Intimate Partner Violence Typologies

Abstract: Typologies of intimate partner violence were developed to describe the heterogeneity of abusive men. They contrast with the traditional feminist ideology of abuser etiology that holds all violence is the result of power and control. Over the past 15 years, a large body of knowledge about typologies has amassed, mostly in sociology journals. Thus, very little typology research has been published in counseling journals. This article synthesizes empirically based typological research and introduces the continuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…CCV does not tend to be a pattern, but rather an intermittent response to occasional conflicts within the couple (Johnson, 1995(Johnson, , 2006. Further evidence has emerged indicating that CCV is the type of violence most likely measured by large random surveys and it shows gender symmetry because both men and women are likely to engage in CCV (Anderson, 2008;Carlson & Jones, 2010;Carney & Barner, 2012;Graham-Kevan & Archer, 2003;Johnson, 1995Johnson, , 2006. Leone et al (2007) found that victims of CCV are less likely to seek out help in shelters or from law enforcement, and are likely to use informal sources of help, including family and friends.…”
Section: The Impact Of Coercive Control On Ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…CCV does not tend to be a pattern, but rather an intermittent response to occasional conflicts within the couple (Johnson, 1995(Johnson, , 2006. Further evidence has emerged indicating that CCV is the type of violence most likely measured by large random surveys and it shows gender symmetry because both men and women are likely to engage in CCV (Anderson, 2008;Carlson & Jones, 2010;Carney & Barner, 2012;Graham-Kevan & Archer, 2003;Johnson, 1995Johnson, , 2006. Leone et al (2007) found that victims of CCV are less likely to seek out help in shelters or from law enforcement, and are likely to use informal sources of help, including family and friends.…”
Section: The Impact Of Coercive Control On Ipvmentioning
confidence: 99%
“…Johnson (1995) identified CCV as resulting from a conflict that gets out of hand and leads to minor forms of violence. This type of violence is not the result of patriarchal domination, rarely escalates, and rarely results in severe injury to the victim (Carlson & Jones, 2010;Johnson, 1995). CCV does not tend to be a pattern, but rather an intermittent response to occasional conflicts within the couple (Johnson, 1995(Johnson, , 2006.…”
Section: The Impact Of Coercive Control On Ipvmentioning
confidence: 99%
“…At the same time, the high IPV incidence rates in LGBTQ relationships (Eaton et al, 2008;McKenry et al, 2006;Turell, 2000) and college students (Allen et al, 2009) underlined IPV as a social and professional issue that stifles healthy development of individuals, relationships, and communities. For instance, the increasingly high incidence rates indicate that counselors working with victims and perpetrators of violence need to be aware of individual factors such as the relationship between biological sex and victimization or perpetration, theory, assessment, and treatment, especially when working with same-sex relationships (Carlson & Jones, 2010;McKenry et al, 2006). In particular, college counseling clinics need to become aware of the results finding that biological sex exhibited a strong relationship with IPV rates and attitudes about IPV.…”
Section: Counseling Implicationsmentioning
confidence: 97%
“…From this perspective, violence is seen as escalating and largely maintained through tactics of power and control perpetrated systematically by men against women (Home of the Duluth Model, 2011). Evidence supporting this approach largely grew from phenomenological studies of women attending to medical facilities, shelters or legal services for domestic violence (Carlson & Jones, 2010). Family Violence Theory, appearing around the same time as…”
Section: Conceptual Definition Of Intimate Partner Violencementioning
confidence: 99%
“…The two main theories that have generally been used to explain the dynamics of intimate partner violence, not specific to the South African context, are Feminist Theory and Family Violence Theory (Kurz as cited in Carlson & Jones, 2010). Feminist theory conceptualizes that IPV is "rooted in patriarchal traditions of male dominance in heterosexual relationships" (Johnson & Leone, 2005, pg.…”
Section: Conceptual Definition Of Intimate Partner Violencementioning
confidence: 99%